Water bamboo plant (Equisetum hyemale) as a phytoremediation agent for water pollution waste - Kurniawati, Septiana; Ulfah, Maria; Nurwahyunani, Atip; Hayat, Muhammad Syaipul (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The aquatic bamboo plant (Equisetum hyemale) can be used as a phytoremediation agent because it has hyperaccumulator properties and is hyper-tolerant of pollutants. With the increasing number of industrial and household activities, managing waste before it is disposed of directly into the environment. This research aims to determine the application of phytoremediation in reducing pollutant content in water pollution waste. The research method was carried out using a literature research design review of the Google Scholar and SINTA databases starting from publication year 2014 to 2023 by reviewing a total of ten national journal articles. The research results show that phytoremediation can reduce wastewater pollution content, especially BOD and COD levels accumulated by the roots of aquatic bamboo plants. The effective time for the phytoremediation method is 3 days, 5 days, and 12 days which can reduce the number of contaminants in sample water according to wastewater quality standards. The novelty of this research is in the variables studied, namely BOD and COD levels using aquatic bamboo plants.